The Reality of the Role of Yemeni Public Universities in Cultural Awareness for Their Students During the Al-Aqsa Flood Battle and Ways to Strengthen It from the Perspective of Their Academic Leaders - Al Sharif, AbdulRaqib Qasim Ali (Journal of Educational and Psychological Sciences, 2025)
This study aimed to identify the reality of the role of Yemeni public universities in raising cultural awareness for their students during the Al-Aqsa Flood Battle and ways to strengthen it from the perspective of their academic leaders. The study used a descriptive-analytical approach, utilizing a questionnaire consisting of 15 items, which was applied to a sample of 31 academic leaders from Yemeni public universities. Using the SPSS statistical program, the study results revealed that the overall mean score of the tool was 4.25 out of 5, reflecting a "high" role. Regarding the two main areas, the reality of the role received an overall mean of 4.20 out of 5, while the area of strengthening cultural awareness received a mean of 4.30 with a rating of "very high importance." Based on these results, the researcher proposed an integrated vision to enhance the role of Yemeni public universities in raising cultural awareness among their students about the Al-Aqsa Flood Battle, along with an action plan for implementation.